Effect of dienogest on serum anti-Mullerian hormone level after laparoscopic cystectomy of ovarian endometrioma - Shih-Shien Weng; Yeou-Lih Wang; Fu-Ching Chuang; Fang-Ju Sun (Elsevier, 2023)
Objective: This comparative study aimed to evaluate the effect of postoperative dienogest treatment on serum anti-Mullerian hormone (AMH) levels in patients undergoing laparoscopic cystectomy of ovarian endometriomas. Materials and methods: A total of 71 patients with ovarian endometriomas treated at our department were enrolled. After surgery, 54 patients received oral dienogest 2 mg daily continuously for 6 months (dienogest group). The other 17 patients did not receive postoperative medical treatment (control group). Serum AMH levels were measured before surgery, at 3-month period after surgery, and at the end of 6-month follow-up period. Serial changes of AMH levels were compared between the two groups. Results: The age, endometrioma size, and serum AMH level before surgery were comparable between the dienogest group and the control group. The AMH levels decreased significantly at 3-month period after surgery in the dienogest group (a decrease of 65.5%; p < 0.001) and the control group (a decrease of 64.8%; p = 0.018). The AMH levels increased gradually from the nadir at 3-month period after surgery and recovered partially at the end of 6-month follow-up period in both groups. There were no statistically significant differences in the rate of reduction of serum AMH levels between the two groups (p = 0.707). Conclusion: Laparoscopic cystectomy of ovarian endometrioma causes a significant decrease in serum AMH levels. The rates of reduction of AMH levels are similar regardless of dienogest treatment. Postoperative dienogest treatment for 6 months has no rescue effect on serum AMH levels in these patients.